Fostering Pancasila Student Profile through Learning Civics at Mis Weigh Opponents - Siti Sarah; Abdul Gani Jamora Nasution (Graduate Program Magister Manajemen Pendidikan, 2023)
This article aims to reveal the implementation and form of fostering the profile of Pancasila students through Civics learning at MIS Timbang Lawan. To explore and uncover meaning in the actual context, this study uses qualitative research with interview, observation, and documentation data collection methods. And the triangulation technique is a way to assess the validity of the data in this study. The results of the study were obtained as follows. First, Civics learning planning understands students in terms of fostering Pancasila student profiles designed in accordance with the school curriculum. Second, the implementation of Civics learning in accordance with the RPP by including the values of profile building on Pancasila in Civics learning. Third, the development of Pancasila student profiles in Civics learning with six main characteristics, Pancasila students represent Indonesian students as lifelong learners who are culturally competent and operate in accordance with Pancasila values which include Faith, piety to God Almighty, ethics, independence, teamwork, cultural diversity, critical thinking, and creativity. The results showed that students were not only intellectually developed but also had a character in accordance with the ideals of Pancasila. Of course, to meet the goals of nation and state, a deeper understanding of inclusion is also needed.